Avian sibling cannibalism: Hoopoe mothers regularly use their last hatched nestlings to feed older siblings - Soler, Juan José; Martín-Vivaldi, Manuel; Nuhlíčková, Soňa; Ruiz-Castellano, Cristina; Mazorra-Alonso, Mónica; Martínez-Renau, Ester; Eckenfellner, Manfred; Svetlík, Ján; Hoi, Herbert (Dōngwùxué yánjiū, 2022)
Sibling cannibalism is relatively common in nature, but its evolution in birds and certain other vertebrates with extended parental care had been discarded. Here, however, we demonstrate its regular occurrence in two European populations of the Eurasian hoopoe ( ) and explore possible adaptive and non-adaptive explanations. Results showed that sibling cannibalism was more frequently detected in Spain (51.7%) than in Austria (5.9%). In these two populations, the hoopoes laid similar clutch sizes, resulting in similar fledging production, but hatching failures were more frequent in the northern population. Consequently, having more nestlings condemned to die in the southern population may explain the higher incidence of sibling cannibalism. In accordance with this interpretation, hatching span and failure, but not breeding date, explained the probability of sibling cannibalism in the Spanish hoopoes, while all three variables predicted brood reduction intensity. Furthermore, experimental food supply reduced the probability of sibling cannibalism, but not the intensity of brood reduction. Finally, females allocated fewer resources to the smallest nestlings when they were going to starve, but not necessarily when they were going to be used as food for their siblings. These results suggest that hoopoes produce extra eggs that, in the case of reduced hatching failure and food scarcity, produce nestlings that are used to feed older siblings. These findings provide the first evidence that sibling cannibalism occurs regularly in a bird species, thus expanding our evolutionary understanding of clutch size, hatching asynchrony, parent-offspring conflict, infanticide, and sibling cannibalism in the animal kingdom.